Avaliação de crianças com síndrome da imunodeficiência humana adquirida, assistidas na unidade de referência municipal de Belém-Pará - MELO, Adriana Miranda (2023)
Introduction: The prevention of the mother-to-child transmission of HIV in Brazil has been extolled by the National Coordination of STD and AIDS to assist to the heterosexual growth and, consequent, reach women of the epidemic, that affect women predominantly in the fertile age and that, therefore, it can place in your risk children. Methodology: Study analytic retrospective, of the traverse type whose casuistry is constituted children, of both sexes, infected by the human immunodeficiency virus (HIV) by vertical transmission, with age among of zero to thirteen years, admitted for accompaniment in the Casa Dia, in the period of august of 1999 to december of 2007. Results: Forty two children were involved on this study. About maternal characteristics: 64,3% of the mothers infected by HIV accomplished prenatal, however, in all the periods of the research the diagnosis of the infection prevailed after the childbirth (92,9%), 97,6%, didn't use ARV during the gestation, in 71,4% there was prevalence of vaginal childbirths. In concern to the infected children's data, 85,7% were born to term, 92,8% received breastfeeding, 95,2% didn't use ARV in the childbirth, 95,2% didn't use ARV neonatal. The age of the occasion of the first consultation prevailed in the age group from 1 to 3 years. The clinic manifestations in the beginning of the disease were: lesions of skin 59,5%, diarrhea 54,8%, pneumonia 54,8% and fever in 40,5% of the children. In all the analyzed periods the dual treatment was the most used (52,3%). Changed of therapeutic outline 51,2% of the analyzed children. 88,1% of the children remaining in the research. Conclusion: It´s necessary to improve services during preganancy in order to the prevention of vertical transmission. HIV infection has been changed a cronical disease and anymore a letal one, being fundamental to increase prevention and treatment.